2011
DOI: 10.1021/ie2007505
|View full text |Cite
|
Sign up to set email alerts
|

Electricity Generation from Wastewater Using an Anaerobic Fluidized Bed Microbial Fuel Cell

Abstract: The anaerobic fluidized bed microbial fuel cell (AFBMFC) was developed to generate electricity while simultaneously treating wastewater. During a complete cycle, the AFBMFC continuously generated electricity with a maximum power density of 1100 mW/m 2 and removal of total chemical oxygen demand (COD) of 89%. To achieve this power density, the artificial electronmediator neutral red (NR) was employed in the anode chamber. Granular biological electrodes, fluidization behavior, electron mediators, and temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 29 publications
(40 reference statements)
1
33
0
Order By: Relevance
“…In comparison to the pH profiles in a non-hybrid dual chamber MFC done in the previous study, similar trend can be observed when operated in the range of [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] C and 20-35 C where the pH of the fresh feed (pH 7.4) reached the minimum value of about 6.2 and 6.7, respectively after operated for 20-25 h before the pH started to move up slowly and finally became almost constant [39]. Nevertheless, it is very difficult to compare this performance with the current study because the previous study was done in a wide range of operating temperatures whereas in the current study, the pH profiles was obtained at each specific operating temperatures.…”
Section: Ph Profilessupporting
confidence: 84%
See 3 more Smart Citations
“…In comparison to the pH profiles in a non-hybrid dual chamber MFC done in the previous study, similar trend can be observed when operated in the range of [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] C and 20-35 C where the pH of the fresh feed (pH 7.4) reached the minimum value of about 6.2 and 6.7, respectively after operated for 20-25 h before the pH started to move up slowly and finally became almost constant [39]. Nevertheless, it is very difficult to compare this performance with the current study because the previous study was done in a wide range of operating temperatures whereas in the current study, the pH profiles was obtained at each specific operating temperatures.…”
Section: Ph Profilessupporting
confidence: 84%
“…Therefore, such phenomenon may affect the substrate utilization rate which therefore minimal substrate is being converted into bio-energy. Low voltage generation at elevated operating temperatures (>40 C) may be due to the denaturation of enzyme which therefore, lead to low voltage generation as a result of poor electrons transfer to the electrode [37]. On top of that, when bacteria was exposed to high temperatures continuously, important elements presented in the cell such as proteins, nucleic acids or other temperature-sensitive matter may suffered an irreversible damage which therefore affect the cell function.…”
Section: Bioenergy Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…In MFC, the electrical power is produced due to microbial oxidation of organic and inorganic constituents of wastewater [70]. The MFC concept is not new; however, there are various configurations of MFC that have recently been tested by different researchers.…”
Section: Energy-generating Treatment Systemsmentioning
confidence: 99%